Nanoencapsulated Dunaliella tertiolecta Extract and β-Carotene in Liposomal Carriers: Antioxidant and Erythroprotective Potential Through Sustained-Release Systems - Jonathan García-Morales; Ricardo Iván González-Vega; Diana Fimbres-Olivarría; Ariadna Thalía Bernal-Mercado; Santiago Pedro Auobourg-Martínez; Karla Alejandra López-Gastélum; Silvia Elena Burruel-Ibarra; María Irene Silvas-García; Andrea Grijalva-Molina; José de Jesús Ornelas-Paz; Carmen Lizette Del-Toro-Sánchez (Molecules, 2025)
The nanoencapsulation of bioactive compounds such as β-carotene and microalgal extracts has emerged as an effective strategy to enhance their stability, bioavailability, and biological efficacy, particularly against oxidative stress. Dunaliella tertiolecta, a microalga rich in carotenoids and chlorophylls, presents notable antioxidant and erythroprotective properties; however, its bioactive potential is limited by low bioaccessibility and degradation during processing and digestion. This study aimed to develop and evaluate nanoliposomes loaded with D. tertiolecta extract and β-carotene as sustained-release systems to improve antioxidant performance and erythroprotective effects. The methodology involved optimizing microalgal cultivation under nitrogen and salinity stress to enhance pigment accumulation, followed by extraction, nanoencapsulation via the particle dispersion method, and physicochemical characterization of the nanoliposomes. Antioxidant capacity and release kinetics were assessed through ABTS and FRAP assays, while erythroprotective activity was evaluated by monitoring oxidative hemolysis in human erythrocytes. The release kinetics revealed an anomalous transport mechanism for both systems, with β-carotene showing faster and more efficient release due to its greater lipophilic compatibility with the nanoliposomal matrix. The nanoliposomal systems demonstrated nanoscale size, high encapsulation efficiency, sustained antioxidant release, and effective erythrocyte protection, with the extract-loaded formulation exhibiting synergistic effects superior to isolated β-carotene. These findings support the potential application of this nanotechnology-based delivery system in functional foods, nutraceuticals, and biomedical formulations aimed at preventing oxidative stress-related cellular damage.